Fibrodysplasia ossificans progressiva: A rare disease with spinal deformity and severe hip dysfunction - Dong Sun; Peng Liu; Zhaolin Wang; Jianhu Mu; Jian Cao (Frontiers Media S.A., 2022)
IntroductionProgressive fibrous dysplasia ossification (FOP) is a rare genetic disease characterized by congenital bone malformations and soft tissue masses that progress to heterotopic ossification. Congenital great toe deformity and progressive heterotopic ossifications with an anatomical and temporal pattern are the two classical clinical characteristics of FOP. We present a unique case of FOP characterized by mandibular angle fascial contracture and back and iliopsoas muscle ossification managed via surgery in a 13 year old girl.Case presentationA 13 year old girl with a history of right cervical fascial release surgery and back heterotopic osteotomy presented to our clinic due to recurrence of heterotopic ossification, scoliosis, and progressive joint stiffness. Computed tomography (CT) or magnetic resonance imaging (MRI) examination confirmed heterotopic ossification of the left back and left iliopsoas muscle and spinal scoliosis. Two years after the surgery, the patient presented with recurrence of back heterotopic ossification and rapidly advancing ossification of the left iliopsoas muscle. Six months after surgery, the patient had no disability, pain and clinical recurrence, and the joint function recovered.ConclusionsIn patients with multiple-site heterotopic ossification caused by FOP, oral function and hip stiffness improve with detailed facial release surgery and rehabilitation treatment. However, dorsal fascia ossification and spinal scoliosis can recur shortly after resection.